Empowering the People’s Economy through MSMEs: Evidence from East east Kotawaringin, Central Kalimantan Indonesia - Mutmainah Mutmainah; Muzalifah Muzalifah; Abdul Helim; Mawar Ardiansyah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to analyze the role of Micro, Small, and Medium Enterprises (MSMEs) in empowering the people’s economy in East Kotawaringin Regency, Central Kalimantan, from the perspective of Islamic economics, particularly based on Surah An-Nisa (4:29). The research employs a qualitative descriptive-analytical approach using library research and supported by limited semi-structured interviews with MSME actors, local government officials, and community religious leaders. Data were analyzed through content and thematic analysis to integrate normative Qur’anic principles with empirical findings. The findings reveal that MSMEs play a strategic role in economic empowerment through employment creation, income generation, and poverty reduction. Optimization can be achieved through human resource development, access to sharia-compliant financing, digital marketing expansion, technological innovation, and halal product certification. Qur’anic values emphasize justice, transparency, mutual consent, and sustainability in economic activities. MSME empowerment grounded in Islamic principles contributes not only to regional economic growth but also to ethical and inclusive development, strengthening the people’s economy in a sustainable manner.